2016
DOI: 10.1002/ange.201510122
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Silver by Glucose

Abstract: Unprecedented silver ion leaching, in the range of 0.7 ppm was seen when metallic silver was heated in water at 70 8 8Ci np resence of simple carbohydrates,s uch as glucose, making it ag reen method of silver extraction. Extraction was facilitated by the presence of anions,s uch as carbonate and phosphate.S tudies confirm at wo-step mechanism of silver release,f irst forming silver ions at the metal surface and later complexation of ionic silver with glucose;such complexes have been detected by mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Baksi et al have shown the mechanism of the extraction of silver by glucose. 7 A similar type of degradation was observed when metal ions (Cu 2+ ) were added to the water in the absence of glucose (Figure S11). No considerable degradation was found in the absence of glucose.…”
Section: Acs Sustainable Chemistry and Engineeringsupporting
confidence: 58%
See 1 more Smart Citation
“…Baksi et al have shown the mechanism of the extraction of silver by glucose. 7 A similar type of degradation was observed when metal ions (Cu 2+ ) were added to the water in the absence of glucose (Figure S11). No considerable degradation was found in the absence of glucose.…”
Section: Acs Sustainable Chemistry and Engineeringsupporting
confidence: 58%
“…Peaks from the material obtained from copper and stainless steel vessels and pure PTFE are shown in Figure 2Aa,b,c, respectively. Peaks labeled as 1, 2, 3, 4, 5, 6, and 7 represent CF 2 wagging (1), CF 2 twisting (2), CF 3 symmetric deformation (3), CF 2 symmetric stretching (4), CF 2 asymmetric stretching (5), C−C stretching (6), and C−F stretching (7), respectively. 5 A new peak was seen at 472 and 473 cm −1 for copper and iron-containing samples, respectively which is absent in pure PTFE.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This result could be attributed to a 1:1 stoichiometry saturation of Ag + ions coordination to IMP, and the excess Ag + ions can interact with the sugar moiety of IMP. 55 Additionally, the influence of IMP concentration on the rheological property of the hydrogels was investigated. For this, hydrogels were obtained by complexation of a fixed concentration of Ag + ions with varying amounts of IMP (50− 100 mM).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The effect of treatments with nanoparticles is always lower with respect to what found with silver salts and as a consequence lower MIC values are found than in the case of ionic silver, see Figure 3 A,C. It has been hypothesized that this is due the easier cellular uptake of silver ions in such conditions, thanks to the formation of Ag + -glucose complexes [ 28 , 29 ] Moreover, also a decreased mobility of nanoparticles in biofilms with respect to ions has to be taken into account [ 30 ]. This is due to their different dimensions and to the trapping effect exerted by EPS (Extracellular Polymeric Substance) on nanoparticles.…”
Section: Resultsmentioning
confidence: 98%